Sistem Pendukung Keputusan Penentuan Profesi Linier Untuk Lulusan Program Studi Sistem Informasi Dengan Metode SAW - Kusumantara, Prisa Marga (ReTII, 2019)
We are facing the era of the industrial revolution 4.0. Technology disruption in all fields, labor/vacancies and unemployment are important issues today. The Ministry of Research, Technology and Higher Education and the Ministry of Manpower in 2017 have stated that the suitability level of the workforce profession with majors/courses during college is still relatively low at 45%. On the other hand, the National Accreditation Agency for Higher Education (BAN-PT) when assessing the study program also measures the degree of linearity between the competencies of graduates with the occupational profession. For this reason, a decision support system exists as a solution to the problems mentioned above. Based on the IS Curriculum 2010 document, the SAW (Simple Additive Weighting) method has been implemented by determining 17 alternatives/professions and 18 criteria/competencies (consisting of 3 levels: significant coverage, some coverage, not required). This system has successfully produced output in the form of a ranking of professions that are most relevant to the competencies of Information Systems graduates. Keyword : decission support, SAW, profession, information system